2008
DOI: 10.1186/1476-4598-7-82
|View full text |Cite
|
Sign up to set email alerts
|

The prince and the pauper. A tale of anticancer targeted agents

Abstract: Cancer rates are set to increase at an alarming rate, from 10 million new cases globally in 2000 to 15 million in 2020. Regarding the pharmacological treatment of cancer, we currently are in the interphase of two treatment eras. The so-called pregenomic therapy which names the traditional cancer drugs, mainly cytotoxic drug types, and post-genomic era-type drugs referring to rationallybased designed. Although there are successful examples of this newer drug discovery approach, most target-specific agents only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(55 citation statements)
references
References 384 publications
(294 reference statements)
0
52
0
2
Order By: Relevance
“…Nevertheless, cancer drug development needs alternative approaches for drug identification because of increasing failure rates, high cost, poor safety, limited efficacy, and a lengthy design and testing process of new entities. In this sense, drug repurposing of established non-cancer drugs that have anticancer activity provides an opportunity to rapidly advance therapeutic strategies in clinical trials (9,10).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, cancer drug development needs alternative approaches for drug identification because of increasing failure rates, high cost, poor safety, limited efficacy, and a lengthy design and testing process of new entities. In this sense, drug repurposing of established non-cancer drugs that have anticancer activity provides an opportunity to rapidly advance therapeutic strategies in clinical trials (9,10).…”
Section: Discussionmentioning
confidence: 99%
“…Repurposing existing drugs is another strategy for drug development in which safety pharmacology studies have been already done, which reduces the time and cost of approving the compounds for clinical use (9,10). Nicotinamide (NAM; pyridine-3-carboxylic acid) is a water-soluble amide active form of vitamin B3 or niacin.…”
Section: Introductionmentioning
confidence: 99%
“…Using a drug repurposing strategy [73], clinical trials have demonstrated the antitumor effect of the combination of hydralazine with valporic acid (a histone deacetylase inhibitor) [74]. Figure 5a shows the comparison of the binding modes of hydralazine with 5-azacytidine.…”
Section: Non-covalent Blockersmentioning
confidence: 99%
“…In addition to the five terms searched for in PubMed, six other terms were identified that were used as synonyms of drug repositioning namely: 'drug re-tasking' [19,20], 'indication switching' [21], 'indication switch' [22], 'therapeutic switching' [19,23], 'indication expansion' [20], 'candidate or compound repurposing' [24]. The terms 'in silico drug repositioning' [15,25,26], 'on-target repositioning' and 'off-target repositioning' [27] were used as a further specification of drug repositioning.…”
Section: Main Findingsmentioning
confidence: 99%